Community Economic Empowerment through Home Industry Activities - Lian Gafar Otaya; Herson Herson (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2023)
This study aimed to explore the role of home industry activities for the community in the Tilongkabila district. This study was qualitative research with a case study method. This study examined in depth the community economic empowerment through home industries that have developed in Bongopini Village (Tofu Tempeh), Lonuo Village (Chips and Sugar Brown), Permata and Bongoime Village (Cake, Pia, workshop, and Ayam Geprek Restaurant), and Tamboo Village (pastry). Furthermore, data were collected through observation, interview, and documentation techniques. Then, data were analyzed based on the interactive model consisting of data reduction, data presentation, and verification/conclusion. This study showed that home industry activities were vital to community economic empowerment. The home industries in the Tilongkabila district have a significant role in reducing unemployment, creating jobs, being a source of income for the community, improving living standards, and increasing community skills. Home industries are a way out of the high gap between people who need work and the number of jobs.